A Study Into Marketing Strategies for Promoting Cultural and Creative Products of Emperor Qinshihuang’s Mausoleum Site Museum in New Era - Yu, Xin (Cultural and religious studies, 2020)
China’s booming economy and the growing demand of urban middle class are creating a favorable situation for the development of domestic cultural and creative industry. The consumption pattern has changed and families spend more outlay on cultural products and services. Within this flourishing industry, many museums caught development opportunities and began to get profit through successfully promoting their own cultural and creative products. However, it is unusual that Emperor Qinshihuang’s Mausoleum Site Museum, enjoying high social status and a reputation for world cultural heritage as well as a national 5A level tourist attraction, regretfully, did not achieve noticeable achievements in this area. Therefore, based on STP theory, the purpose of this paper is to study the reasons why this museum fails to fulfill its potential in promising cultural and creative industry and give some suggestions to the development and promotion of its cultural and creative goods.